The Mediating Role of Employee Engagement in the Relationship between Training, Customer Loyalty Programs, and Job Satisfaction: A Study of Five-Star Hotels in Indonesia - Hikmah, Lailatul (Smart International Management Journal, 2026)
The hospitality industry, particularly five-star hotels, increasingly faces the challenge of maintaining service excellence while ensuring employee well-being and organizational sustainability, thereby raising critical questions regarding how managerial practices such as training and customer loyalty programs influence job satisfaction through employee engagement. This study aims to examine the mediating role of employee engagement in the relationship between training effectiveness, customer loyalty program implementation, and employee job satisfaction in Indonesian luxury hotels. A quantitative explanatory approach was employed using survey data collected from full-time hotel employees, which were subsequently analyzed through structural equation modeling (SEM) to evaluate both direct and indirect relationships among variables. The results indicate that training and customer loyalty programs positively influence job satisfaction, with employee engagement demonstrating a significant mediating effect that strengthens these relationships. These findings suggest that psychological involvement functions as a crucial interpretive mechanism through which organizational initiatives are translated into positive employee attitudes. The study concludes that integrating human resource development and customer-oriented strategies with engagement-focused management practices is essential for achieving sustainable service performance and workforce stability in high-end hospitality contexts.